Introducing Audio Podcasts into a Practical Laboratory Course for Pharmacy Students as a Novel Tool for Performance Assessment - Daniel Baecker (MDPI AG, 2022)
The use of digital tools can positively impact higher education for both scholars and faculty. In recent years, it has become apparent that podcasts are a suitable medium for use in teaching. They are provided almost exclusively by lecturers for students, with students passively listening to them rather than actively participating in their production. However, this could also be valuable for students. Therefore, this pilot study investigated the extent to which the creation of a podcast would be accepted by students as a method for capturing pharmacy students' understanding of the learning content. The evaluation was performed as part of the "Clinical Chemistry" practical course, which was attended by third-year pharmacy students in groups of three. After passing the station dealing with practical clinical chemistry relevant diagnostic systems, the groups were asked to produce an educational podcast covering the essential content on the topics of urine test strips or pulse oximetry, respectively. Student attitudes toward the adoption of podcasts as a tool for performance assessment were determined with an anonymous and voluntary survey. The respondents reported that they had fun creating the podcast, which enabled them to look at the instructional content from a different perspective. Competencies such as social and communication skills and media literacy as well as self-organized and self-directed learning were also promoted. However, the students assumed that the tool is not ideally suited for dealing with extensive topics. Nonetheless, the students clearly support the continued creation of podcasts as a performance assessment tool. In addition, they suggest integrating podcasts into other courses within the pharmacy curriculum. This may also be related to the infrequent use of novel technologies, such as podcasts, in their education thus far.